(untitled) (UNWE Yearbook, 2011)
This study is dedicated to the impact of the global financial and economic crisis on the Bulgarian banking market, since it has the largest share in the financial system and historically is established as the primary source of funding in the economy. The banks behaviour is studied on the inter-bank market and as well as in the process of financial intermediation. The global nature of the crisis and the view that our economy is similar to the new EU Member States of CEE, justify a comparative study of markets in eight of these countries and their relationship with the market in the euro area. Analysis shows that, in tranquil periods, interest rates on unsecured overnight deposits fluctuate around the main monetary policy rate and for the countries with a fixed exchange rate, including Bulgaria, the main policy rate of the ECB serves as an anchor. In crisis periods this connection is violated, and the interest rates and associated indicators show a significantly larger volatility.Due to the countercyclical policy of BNB since 2008 the Bulgarian banking system builds capital over its regulatory minimum, which reaches 3 bln. BGN as compared to the 12% capital adequacy recommendation level. Thus notwithstanding the impact of the global financial crisis, the Bulgarian banking system preserves its high capital buffers. The main risks of the banking sector activity are the rising share of non-performing loans and shrinking profits, but at this stage the credit institutions as part of the cross-border banking groups can and continue, though to a lower extent, to rely on parent banks’ financing.The systemic nature of the global financial and economic crisis reveals the fact that isolated markets don’t exist and therefore the problems should be resolved in a global and coordinated manner if we want to limit the duration, the depth and the economic costs of the future financial crises.